The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1364/ol.39.003579
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast laser fabrication of Bragg waveguides in chalcogenide glass

Abstract: Bragg waveguides are fundamental components in photonic integrated circuits and are particularly interesting for mid-IR applications in high index, highly nonlinear materials. In this work, we present Bragg waveguides fabricated in bulk chalcogenide glass using an ultrafast laser. Waveguides with near circularly symmetric cross sections and low propagation loss are obtained through spatial and temporal beam shaping. Using a single-pass technique, the waveguide and Bragg structure are formed at the same time. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
6
0
1
Order By: Relevance
“…A new approach was therefore needed to fabricate WBGs suitable for sapphire fibers requiring high temperature stability. We developed a three-step process as follows: The WBG fabrication method is similar to one employed for bulk glass material [30], where the refractive index modulation is formed by utilizing the intrinsic shape of the Gaussian beam along the beam propagation direction. Figure 6(c) shows the top-view of a fabricated WBG structure.…”
Section: Single-mode Waveguide Bragg Gratings In Planar Sapphirementioning
confidence: 99%
“…A new approach was therefore needed to fabricate WBGs suitable for sapphire fibers requiring high temperature stability. We developed a three-step process as follows: The WBG fabrication method is similar to one employed for bulk glass material [30], where the refractive index modulation is formed by utilizing the intrinsic shape of the Gaussian beam along the beam propagation direction. Figure 6(c) shows the top-view of a fabricated WBG structure.…”
Section: Single-mode Waveguide Bragg Gratings In Planar Sapphirementioning
confidence: 99%
“…For comparison, Table 1 lists κ values for The duty cycle was fixed at 35%, whereas the writing pulse energy was varied. [21] PbP 1551 25 -Boro-aluminosilicate (Eagle2000) [22] PbP 1551 145 0.6 Boro-aluminosilicate (Eagle2000) [23] PbP 1550 472 0.5 Soda-lime [27] Two-step PbP 1577 14 -Fused silica [26] Modulated burst 1548 111 1.5 Er:Yb codoped phosphate [30] Modulated burst 1537 242 -Yb-doped phosphate [42] Modulated burst 1535 221 -Boro-aluminosilicate (Eagle2000) [31] Modulated burst 1551 713 -Fused silica [43] Modulated burst 1546 36 0.7 Boro-aluminosilicate (Eagle2000) [24] PbP 799 65 -Boro-aluminosilicate (Eagle2000) [28] Modulated burst 1552 157 -ZBLAN [29] PbP überstructure 1550 324 -Boro-aluminosilicate (Eagle2000) [44] Multiscan modulated burst 1563 177 -LiNbO 3 [45] Modulated burst stressors 1540 45 -Boro-aluminosilicate (Eagle2000) [41] PbP 648 136 -Boro-aluminosilicate (Eagle2000) [41] PbP 698 183 0.8 Boro-aluminosilicate (Eagle2000) [41] PbP 748 187 -Boro-aluminosilicate (Eagle2000) [41] PbP 798 163 -Fused silica [46] Modulated burst 1550 210 2.2 Fused silica [47] Modulated burst 1549 280 < 1 Chalcogenide (GLS) [48] Modulated burst 1551 179 -LiNbO 3 [49] Multiscan modulated burst (depressed clad) 1558 1230 1.52-3.51 Boro-aluminosilicate (Eagle2000) [50] Two-step PbP 1545 120 -Fused silica [25] PbP (waveguide bundle) 840 126 -Fused silica [25] PbP (waveguide bundle) 1550 220 1.6 Borosilicate (AF45) [51] Modulated …”
Section: Coupling Coefficient κmentioning
confidence: 99%
“…Chalcogenides being transparent up to 5 mm are a potential host for this application. Through spatial and temporal beam shaping, McMillen et al reported WBGs with circular cross-sections in GLS chalcogenide glass [48]. The strongest WBGs were written with a 25% duty cycle, were single mode at 1550 nm, and had grating depths of up to 25 dB.…”
Section: Chalcogenidementioning
confidence: 99%
“…Прямая фемтосекундная запись является перспективной безмасочной и ши-роко распространенной технологией создания оптических волноводов в объеме стекол и кри-сталлов [1][2][3][4][5][6][7]. Оптические стекла и кристаллы могут быть разделены на три группы на осно-ве знака постоянно изменяющегося показателя преломления (ПП): 1) материалы, ПП которых увеличивается при фемтосекундной микрообработке; 2) материалы, ПП которых понижается;…”
Section: ключевые слова: лазерно-индуцированное воздействие фемтосекunclassified